Perbankan Syariah dalam Perspektif Hukum Perdata dan Pidana Serta Perbandingan Sistem Perbankan Syariah Global - Renaldi Ikhsan; Muhammad Fadhil; Nurnasrina (Yayasan Mutiara Hati Moeslem, 2026)
Islamic banking is a financial system based on Islamic principles, including the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling), while emphasizing justice and public welfare in economic activities. This study aims to analyze Islamic banking from the perspectives of civil law and criminal law in Indonesia, as well as to compare the implementation of Islamic banking systems at the global level. The research employs a normative juridical method using a statutory, conceptual, and comparative approach, supported by an analysis of relevant laws, regulations, legal doctrines, and scholarly literature. The results indicate that, from a civil law perspective, the legal relationship between Islamic banks and customers is based on sharia contracts (akad) that function as binding agreements under general contract law, with specific characteristics derived from sharia principles. From a criminal law perspective, Islamic banking institutions remain subject to general and special criminal provisions, particularly in cases involving banking crimes, fraud, and money laundering, without exemption due to their sharia-based nature. Furthermore, the global comparison shows significant variations in Islamic banking systems, where some countries fully adopt Islamic banking, while others apply a dual banking system or integrate Islamic banking within conventional financial frameworks. These differences are influenced by national legal systems, regulatory policies, and institutional support. This study concludes that Islamic banking represents not only a religious-based economic system but also a complex legal entity that interacts closely with civil law, criminal law, and global legal dynamics.